Clinicoradiologic features distinguish tumefactive multiple sclerosis from CNS neoplasms. Issue 1 (February 2017) - Lin, Xuling; Yu, Wai-Yung; Liauw, Lishya; Chander, Russell Jude; Soon, Weiling E.; Lee, Hwei Yee; Tan, Kevin
Abstract: Background: There are limited data to guide clinicians in differentiating tumefactive multiple sclerosis (TMS) from CNS neoplasms. Identifying distinguishing features will inform diagnosis and management and avoid unnecessary diagnostic biopsy. Our study aimed to determine the clinical and radiologic features that differentiate TMS from glioma and CNS lymphoma (CNSL) in patients who present with tumefactive lesions. Methods: We retrospectively reviewed all patients with tumefactive lesions and histologically proven or clinically diagnosed TMS, glioma, or CNSL at our tertiary center from 1999 to 2012. Two independent blinded neuroradiologists rated MRI brain scans at presentation. We correlated patients' demographic, clinical, laboratory, and radiologic data to final diagnosis. Results: A total of 133 patients (10 TMS, 85 glioma, 38 CNSL) were analyzed. Patients with TMS were younger and a greater proportion were women. Presenting symptoms did not distinguish between diagnoses. TMS lesions were smaller compared to glioma and CNSL, had no or mild mass effect, and were always associated with contrast enhancement. Radiologic features that were more frequent in TMS lesions were incomplete rim (open-ring) enhancement, incomplete peripheral diffusion restriction, and mixed T2 signal and CT hypoattenuation of MRI-enhancing components (all p < 0.05). Conclusions: Radiologic features but not presenting symptoms are useful in distinguishing TMS from CNS neoplasms.